Chronic pain among older people in Malaysia: Prevalence, associated factors and healthcare utilization / Lily Rafidah Mohamed Zaki - Lily Rafidah, Mohamed Zaki (2016)
Pain is an unpleasant experience that serves as a warning for the individual to withdraw from damaging situations and protect oneself against injury. However, when pain becomes chronic, it stops from being protective and instead becomes a threat to the individual. Chronic pain is defined as a form of pain that lasts for three months or more, or a form of pain that persists beyond the normal period of tissue healing, which is typically three months. Many studies on chronic pain have been carried out in developed countries, however data are sparse in middle-income country, such as Malaysia. To fill this gap, this research aims to describe the prevalence and correlates of chronic pain among older people in Malaysia and its association with obesity, psychiatric morbidity and healthcare utilization. The study was conducted using a national representative data from the Third National Health and Morbidity Survey (NHMS III). This thesis analyses the subpopulation data of older people aged 60 and above (n=4954) from the NHMS III. Analysis was conducted using Survey Data Analysis in STATA to account for complex sample data. The findings revealed that the prevalence of chronic pain among older people in Malaysia is high, amounting to 15.6% (95% CI: 14.5, 16.8). Among 755 older people with chronic pain, 655 (88.3%) reported some level of interference on their daily activities. Socio-demographic characteristics that were significantly related to chronic pain among older people includes female gender (PR= 1.50, 95% CI= 1.31, 1.72), Indian ethnicity (PR= 1.45, 95% CI= 1.14, 1.84), widow or widower group (PR= 2.70, 95% CI= 1.24, 5.91) and those with no formal education background (PR=2.25, 95% CI= 1.72, 2.95). Whereas, health-related factors that were associated with chronic pain in older people were presence of comorbidities (PR= 1.31, 95% CI= 1.12, 1.54) where increase in the number of comorbidities increased the risk as well (PR=1.69, 95% CI= 1.44, 1.99). Presence of abdominal obesity (PR=1.62, 95% CI=1.42, 1.86) and overweight and obesity (PR=1.23, 95% CI=1.06, 1.44) were also related to chronic pain in older people. iv However, presence of psychiatric morbidity was not significantly associated with chronic pain. Chronic pain in older people also significantly related to higher frequency of hospitalization. After adjusting for important confounders, chronic pain remained as a significant factor (IRR of 1.69, 95% CI: 1.24, 2.31). Pain interference, level of interference and ambulatory care visits were not significantly associated with chronic pain in older people. Instead, higher level of chronic pain interference among older people was found to reduce the number of visits to ambulatory care facilities. This study provides additional insights on the chronic pain problem among older people in Malaysia. It is hoped that the findings of this research will be used as a basis to establish chronic pain policy in Malaysia especially among older people, thus expanding and improving current services of older people in Malaysia.